27 The cardiac conduction system revealed by microct of archive samples. (2nd February 2018) - Jarvis, JC; Stephenson, RS; Anderson, R; Guerrero, R; Jones, C
Abstract : Purpose: To make iodine contrast-enhanced micro CT scans of two congenitally malformed hearts from an archive consented in the 1970s. Methods: Based on their size and wall thickness, we immersed the samples for two weeks in 3.75% iodine/potassium iodide in formalin, changing to fresh solution after one week. We took small samples prior to iodine infusion for potential future genetic analysis. Micro-CT imaging of the entire samples produced 3D tomographic images with isometric voxels of 27 microns. We made scans at higher resolution using fields of view that contained subsets of the sample. Results This new technique confers great medical value on archived samples, because the technique provides a complete visualisation of the micro anatomy of the working myocardium, the cardiac conduction system, the vascular supply and great vessels, the valves, and where present the traces of restorative interventions. Although the cardiac chambers had previously been opened for post mortem inspection, it was possible to bind the samples in clingfilm so that the scans were easily interpreted as if undisturbed. The iodine contrast agent can be leached out of the tissue after scanning. Conclusion: The morphological structure of these samples is now preserved for the rest of time. The data can be distributed as digital files, visualised with ubiquitous software and segmented to reveal components such as the conduction tissues. Visualisation can be achieved in any sectional plane or 3-dimensional attitude. The technique offers a stepwise change in the investigation of archived tissues.